Underlying ethics in economic theory (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
In the last few years, many authors have introduced the inherent discretion to the human being to their theories and economical models. The normative regulation defines and motivates people to do or not some actions, being indispensable its consideration in the analysis. This paper begins with the definition of economy and its basics concepts, then it makes a brief revision of pioneer theories which contemplate the personal discretion and its actions and it finishes with the ethical and moral influence in the economical development in a country.
Keywords: economy; ethics; politics; regulation; development